Optimalisasi Pemasaran Menggunakan E-Commerce Untuk Peningkatan Penjualan Mie Aceh - Putri Intan Suri; Helen Parkhust; Faradina Zevaya (STIKes Ibnu Sina Ajibarang, 2024)
Ujungalang Village is a lagoon island located in Segara Anakan. Because of this geographical condition, Ujungalang Village has different types of plants from those on the mainland. One of the plants that grow in Ujungalang Village is the Nipah tree. In Ujungalang Village, especially Motean Hamlet, nipah sales are limited to dried nipah without any processing. The processing of nipah sticks is not maximized, making the selling price of nipah sticks low. Therefore, training activities on nipah stick weaving were carried out as an effort to improve the economy and productivity of PKK women in Motean Hamlet, Ujungalang Village. The service activities consisted of the preparation stage and the practice stage. The evaluation results of the service activity showed an increase in the level of knowledge of the Ujungalang Village community about the importance of processing nipah sticks. Not only the community, the Ujungalang village also responded positively to this training activity. The results of this plate-making training activity from nipah sticks have a very positive impact on introducing the potential of nipah sticks and their economic value to support the productivity of PKK women in Ujungalang Village.